Paul's understanding of spiritual formation: Christian formation and impartation - Chung, Michael (2009)
'Spiritual formation' is a popular term today, but definitions of its meaning vary. It is usually thought of from the perspective of the disciple rather than from the perspective of the mentor, who accompanies and guides the disciple in the formation process. This thesis seeks to contribute to a greater understanding of the spiritual formation process by a close examination of Paul's perspective as one forming the protégé.